2011
DOI: 10.1136/aim.2010.003269
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Massage Therapy for Neuropathic Pain following Spinal Cord Injury: An Exploratory Study

Abstract: ObjectiveThe study sought to explore the possibility of using acupuncture and massage therapy for relieving neuropathic pain following spinal cord injury (SCI). Design 30 individuals with SCI and neuropathic pain were assigned to treatment of either massage or acupuncture, with 15 individuals in each group. Both groups received treatment twice weekly for 6 weeks. Treatments were evaluated at the end of treatment and 2 months later (follow-up).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 34 publications
1
34
0
1
Order By: Relevance
“…A prospective-controlled trial, which included a comparison between acupuncture and massage, found that massage did not produce a significant reduction compared with acupuncture in SCI-related NP intensity. 52 No evidence was found on efficacy of massage on its own.…”
Section: ) Treatments With Low-quality Evidence Of Positive Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective-controlled trial, which included a comparison between acupuncture and massage, found that massage did not produce a significant reduction compared with acupuncture in SCI-related NP intensity. 52 No evidence was found on efficacy of massage on its own.…”
Section: ) Treatments With Low-quality Evidence Of Positive Effectmentioning
confidence: 99%
“…70 In another study, 8 of 15 patients with SCI-related NP responded to acupuncture. 52 A retrospective observational case series of patients with traumatic or nontraumatic SCI found a significant improvement in pain for bilateral, for bilateral, symmetric, burning or constant pain compared with unilateral, asymmetric, atypical or intermittent pain. 71 Studies of acupuncture suffer from a lack of standardization of process or procedure delivery and practice principles, and evidence for effectiveness is inconclusive.…”
Section: Intravenous Lidocainementioning
confidence: 99%
“…(45)(46)(47)(48) MT has also been shown to be effective for decreasing neuropathic pain in some people with spinal cord injury. (27) Roberts (28) reported that light to moderate massage led to a decrease in the gain of the spinal nociceptive reflexes, which are often elevated in chronic pain syndromes. Although we did not explore potential mechanisms for the changes seen in our participants with MS, MT may also be effective in decreasing pain in people with MS through mechanisms similar to those described by Roberts.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Approximately a third of surveyed individuals with MS report they use massage therapy (MT) as an adjunct to their medical treatment, often because conventional treatments are not effective in managing their symptoms. (20,21) While various lines of research demonstrate that MT can improve QOL in people with MS, (21)(22)(23)(24)(25) and decrease fatigue, pain, and spasticity in other patient populations, (26)(27)(28)(29)(30)(31)(32)(33) there is little empirical Participants were recruited by word of mouth, RRC-approved fliers, and through the patient database at the Shepherd Center in Atlanta, Georgia. We aimed to enroll 25 participants; thus, if a participant dropped out of the study, we recruited another in order to complete data collection on 25 people with MS. All participants received the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…So, elongated needle therapy has a good effect on the treatment of depth of disease. Studies have shown that acupuncture treatment for SCI was significantly effective, reduced both pain and improved the postoperative rehabilitation efficacy [11], and we found to treat urinary retention after spinal cord injury. The elongated needle therapy was better than general acupuncture method which is effective to increase the amplitude and incubate time of SCEP and improved urinary retention [12,13].…”
Section: Introductionmentioning
confidence: 86%